2022
DOI: 10.3390/ma15124178
|View full text |Cite
|
Sign up to set email alerts
|

Improvements of Flexural Properties and Thermal Performance in Thin Geopolymer Based on Fly Ash and Ladle Furnace Slag Using Borax Decahydrates

Abstract: This paper elucidates the influence of borax decahydrate addition on the flexural and thermal properties of 10 mm thin fly ash/ladle furnace slag (FAS) geopolymers. The borax decahydrate (2, 4, 6, and 8 wt.%) was incorporated to produce FAB geopolymers. Heat treatment was applied with temperature ranges of 300 °C, 600 °C, 900 °C, 1000 °C and 1100 °C. Unexposed FAB geopolymers experienced a drop in strength due to a looser matrix with higher porosity. However, borax decahydrate inclusion significantly enhanced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 56 publications
(95 reference statements)
0
5
0
Order By: Relevance
“…In comparison, the 10 years curing age samples had lower overall porosity, pore diameter, and pore volume than the 28 days curing age sample. The reduction in total porosity is due to longer evaporation and dehydroxylation in the geopolymer during the curing period, which generates an isolated pores network and yields a denser surface [ 11 ]. This observation is consistent with the finding of surface morphology ( Figure 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In comparison, the 10 years curing age samples had lower overall porosity, pore diameter, and pore volume than the 28 days curing age sample. The reduction in total porosity is due to longer evaporation and dehydroxylation in the geopolymer during the curing period, which generates an isolated pores network and yields a denser surface [ 11 ]. This observation is consistent with the finding of surface morphology ( Figure 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Otherwise, if standard X-ray tomography (µ-CT) is utilized, it is difficult to obtain a highlight-connected pore network for geopolymer material from the segmented pore [ 10 ]. Synchrotron X-ray tomography (SXTM) produces a high-resolution three-dimensional picture of pores and network arrangement [ 11 ]. Evaluating the microstructural properties of geopolymer in the short and long term is critical for identifying potential changes of structure degradation.…”
Section: Introductionmentioning
confidence: 99%
“…The use of LF slag alone [60], activated LF slag, and the inclusion of additives like fly ash [129][130][131][132][133][134][135][136][137][138][139][140], fibers [141][142][143], and metakaolin [59,144] has been studied for forming geopolymers. The most critical factor in developing geopolymers is the hydration of binders, cement, slag, or fly ash to activate calcium aluminum silicate minerals using an alkali activator.…”
Section: Lf Slag-based Geopolymersmentioning
confidence: 99%
“…It has been observed that the bending performance of thin borax decahydrate geopolymers increases significantly with temperature increase. Thus, it has been seen that geopolymers containing borax decahydrate can be used to develop high strength [69]. Nano carbon black was used in a study on thermal conductivity and photothermal conversion.…”
Section: Tga-dta Analysismentioning
confidence: 99%